Ornament and figure in Graeco-Roman art: rethinking visual ontologies in classical antiquity - Dietrich, Nikolaus; Squire, Michael (De Gruyter, 2018)
"This edited collection explores the relationship between 'ornament' and 'figure' in Graeco-Roman antiquity. Through a series of specially commissioned chapters, contributors examine a range of ancient materials and texts: combining theoretical discussion and close analytical interpretations, the book interrogates shifting ideas of the image in both antiquity and the ensuing western art critical tradition"--